Simultaneous field‐aligned currents at Swarm and Cluster satellites. Issue 10 (23rd May 2015) - Dunlop, M. W.; Yang, J.‐Y.; Yang, Y.‐Y.; Xiong, C.; Lühr, H.; Bogdanova, Y. V.; Shen, C.; Olsen, N.; Zhang, Q.‐H.; Cao, J.‐B.; Fu, H.‐S.; Liu, W.‐L.; et al.
Abstract We show for the first time, with direct, multispacecraft calculations of electric current density, and other methods, matched signatures of field‐aligned currents (FACs) sampled simultaneously near the ionosphere at low (~500 km altitude) orbit and in the magnetosphere at medium (~2.5 RE altitude) orbits using a particular Swarm and Cluster conjunction. The Cluster signatures are interpreted and ordered through joint mapping of the ground/magnetospheric footprints and estimation of the auroral zone boundaries (taken as indication of the boundaries of Region 1 and Region 2 currents). We find clear evidence of both small‐scale and large‐scale FACs and clear matching of the behavior and structure of the large‐scale currents at both Cluster and Swarm. The methodology is made possible through the joint operations of Cluster and Swarm, which contain, in the first several months of Swarm operations, a number of close three‐spacecraft configurations.